2008
DOI: 10.1097/01.ccm.0000297955.02633.a4
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 increases survival and reduces the development of lung edema induced by endotoxin administration in a murine model of acute lung injury

Abstract: These data show that adenoviral mediated expression of angiopoietin-1 can protect against the development of lung capillary protein leak and decrease the mortality induced by endotoxin. However, the timing of AdAng1 administration in relation to the onset of lung injury may be critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
0
29
2
Order By: Relevance
“…Although Ang-1 was preventing development of these important aspects of VILI, it did not influence the end points of VILI such as vascular leakage and impaired gas exchange (Hegeman et al, 2010). Our data are in apparent contrast with previously reported protective effects of Ang-1 on vascular leakage in endotoxin-challenged animals (Huang et al, 2008;McCarter et al, 2007;Mei et al, 2007;Witzenbichler et al, 2005). Using a similar dosing and administration procedure of Ang-1, David et al showed that Ang-1 therapy also stabilized endothelial barrier function in an murine model of polymicrobiological abdominal sepsis as evidenced by attenuation of protein leakage from lung capillaries into the alveolar compartment (David et al, 2011).…”
Section: Inhibition Of Ventilator-induced Lung Inflammation: Does It contrasting
confidence: 99%
“…Although Ang-1 was preventing development of these important aspects of VILI, it did not influence the end points of VILI such as vascular leakage and impaired gas exchange (Hegeman et al, 2010). Our data are in apparent contrast with previously reported protective effects of Ang-1 on vascular leakage in endotoxin-challenged animals (Huang et al, 2008;McCarter et al, 2007;Mei et al, 2007;Witzenbichler et al, 2005). Using a similar dosing and administration procedure of Ang-1, David et al showed that Ang-1 therapy also stabilized endothelial barrier function in an murine model of polymicrobiological abdominal sepsis as evidenced by attenuation of protein leakage from lung capillaries into the alveolar compartment (David et al, 2011).…”
Section: Inhibition Of Ventilator-induced Lung Inflammation: Does It contrasting
confidence: 99%
“…In a murine model of LPS-induced lung injury, time-dependent increase in VEGF and decrease in Ang-1 and Ang-4 expression were observed in the lung, which were associated with increased neutrophil influx and BAL protein concentrations (108). In addition, pretreatment with an adenovirus expressing the Ang-1 transgene reduced vascular leakiness brought on by transient adenoviral-mediated VEGF expression (247) or by systemic endotoxin administration (96). Ang-1 also decreases endothelial cell apoptosis (125) and inhibits adhesion molecule expression on endothelial cells exposed to inflammatory cytokines, thereby reducing leukocyte adhesion (112).…”
Section: Angiopoietins and Vegfmentioning
confidence: 95%
“…In experimental models of acute lung injury, transgenic Ang-1 overexpression or treatment led to reduced cytokine and adhesion molecule expression, polymorphonuclear infiltration and vascular leakage in the lung [87][88][89][90]. Although endothelial barrier-protective properties of Ang-1 have been demonstrated in several studies [87][88][89][91][92][93], the methods of Ang-1 application, e.g. gene therapy or cell-based delivery, are far from translation into clinical therapies.…”
Section: Improving Pulmonary Barrier Functionmentioning
confidence: 99%